The Application of Delone and Mclean Framework to Analyze the Relationship Between Customer Satisfaction and User Experience of Mobile Application - Bekti Setiadi; Kraugusteeliana K; Andriya Risdwiyanto; Asri Ady Bakri; Ilham Arief (SEULANGA SYSTEM PUBLISHER, 2023)
This study aims to determine how much user satisfaction is based on the influence of the user experience of e-commerce applications using the modified DeLone & McLean model by adding perceived utilitarian and perceived hedonic variables as the main dimensions representing the IT user experience. The population of this research is users of e-commerce applications as buyers using the purposive sampling technique. While data analysis uses the PLS-SEM approach with the help of SmartPLS. The study's findings show that while perceived utilitarianism and service quality have little bearing on user satisfaction, perceived hedonistic behavior, system quality, and information quality do. Three of the many hypotheses that were put forth and rejected were: the influence of service quality on user contentment and use, and the influence of perceived utilitarianism on user satisfaction.